Integration of Protein-Protein Interaction Networks and Gene Expression Profiles Helps Detect Pancreatic Adenocarcinoma Candidate Genes - Su, Lili; Liu, Guang; Guo, Ying; Zhang, Xuanping; Zhu, Xiaoyan; Wang, Jiayin (Frontiers in Genetics, 2022)
More and more cancer-associated genes (CAGs) are being identified with the development of biological mechanism research. Integrative analysis of protein-protein interaction (PPI) networks and co-expression patterns of these genes can help identify new disease-associated genes and clarify their importance in specific diseases. This study proposes a PPI network and co-expression integration analysis model (PRNet) to integrate PPI networks and gene co-expression patterns to identify potential risk causative genes for pancreatic adenocarcinoma (PAAD). We scored the importance of the candidate genes by constructing a high-confidence co-expression-based edge-weighted PPI network, extracting protein regulatory sub-networks by random walk algorithm, constructing disease-specific networks based on known CAGs, and scoring the genes of the sub-networks with the PageRank algorithm. The results showed that our screened top-ranked genes were more critical in tumours relative to the known CAGs list and significantly differentiated the overall survival of PAAD patients. These results suggest that the PRNet method of ranking cancer-associated genes can identify new disease-associated genes and is more informative than the original CAGs list, which can help investigators to screen potential biomarkers for validation and molecular mechanism exploration.